Geoenvironmental engineering geoenvironmental impact management : proceedings of the third conference organized by the British Geotechnical Association and Cardiff School of Engineering, Cardiff University, and held in Edinburgh on 17-19 September 2001 - Yong, R. N.; Thomas, H. R. (Thomas Telford, 2001)
'Geoenvironmental Engineering' contains the collected papers from the third Geoenvironmental Engineering Conference, organised by the British Geotechnical Association and Cardiff School of Engineering, Cardiff University. Authors from around the world have submitted the papers in this volume. The theme of this 3rd conference is geoenvironmental impact management.